Rural transformations and rural policies in the US and UK - Shucksmith, Mark. (New York : Routledge, 2012)
'This book examines the transformations of rural society and economy in the UK and US during the last half-century, and explores the significance of these trends and changes for community sustainability, quality of life and the environment. While both the UK and US are highly urbanised, rural people and communities continue to contribute to national identity, economic development and social solidarity, as well as to environmental quality. Contributors explore the degree to which rural people exhibit agency and autonomy, rather than being merely passive in the face of exogenous forces of change in a globalised world. They also illuminate very different policy approaches to rural policy in two advanced capitalist societies often thought to be similar, and show how fundamental differences in rural policy approaches of the US and the UK are based on different social ideologies and values that shape policies relating to rural areas. This book will help to stimulate transatlantic dialogue on rural scholarship and rural policy analysis, while also contributing to theory and policy development. It will be of interest to researchers, students and everyone involved in the policy and practice of rural development.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Rural development -- United States; Rural development -- United Kingdom; Sociology, Rural; United States -- Rural conditions; Great Britain -- Rural conditions